Position Control of 3-DOF Experimental Articulated Robot Arm using PID Controller - Vo, Dinh-Hieu; Le, Nam-Chau; Nguyen, Thi-Y-Nhi; Huynh, Tran-Phuong; Huynh, Nhat-Truong; Tran, Kim-Huy; Nguyen, Ba-Chinh; Do, Truong-Giang; Tran, Gia-Huy; Nguyen, Van-Dong-Hai (Peneliti Teknologi Teknik Indonesia, 2025)
In this paper, we are simulating a 3-degrees of freedom (DOF) Articulated Robot Arm, calculating kinematics and building a PID controller for the 3-Dof Articulated Robot Arm. First, the design process of the 3-Dof robot arm model is done on the Solid works platform. Second, the PID control method is used to determine the